New combinations in Tarenaya (Cleomaceae) for the Argentinian flora - Arana, Marcelo D.; Oggero, Antonia J. (Phytotaxa, 2016)
In the present work new combinations are made for three South American species originally described under Cleome: Tarenaya cordobensis, T. lilloi and T. tucumanensis.